The Effect of Balance Training on Postural Control in Patients with Parkinson’s Disease Using a Virtual Rehabilitation System - Albiol-Pérez, Sergio; Gil-Gómez, José-Antonio; Muñoz-Tomás, Maria-Teresa; Gil-Gómez, Hermenegildo; Vial-Escolano, Raquel; Lozano-Quilis, José-Antonio (Methods of Information in Medicine, 2017)
Objectives: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor clinical alterations among others. Postural problems have serious consequences for patients, not only limiting their daily life but also increasing some risks, like the risk of fall. Inadequate postural control and postural instability is a major problem in PD patients. A Virtual Motor Rehabilitation System (VMR) has been tested in patients with PD in the intervention period. Our purpose was to analyze the evolution of the spatial postural control during the intervention period, to see if there are any changes caused precisely by this intervention.Methods: Ten people with PD carried out 15 virtual rehabilitation sessions. We tested a groundbreaking system based on Virtual Motor Rehabilitation in two periods of time (baseline evaluation and final evaluation). In the training sessions, the participants performed a customizable treatment using a low-cost system, the Active Balance Rehabilitation system (ABAR). We stored the pressure performed by the participants every five hundredths of a second, and we analyzed the patients’ pressure when they maintained their body on the left, on the right, and in the center in sitting position. Our system was able to measure postural control in every patient in each of the virtual rehabilitation sessions.Results: There are no significant differences in the performance of postural control in any of the positions evaluated throughout the sessions. Moreover, the results show a trend to an improvement in all positions. This improvement is especially remarkable in the left/right positions, which are the most important positions in order to avoid problems such as the risk of fall. With regard to the suitability of the ABAR system, we have found outstanding results in enjoyment, success, clarity, and helpfulness.Conclusions: Although PD is a progressive neurodegenerative disorder, the results demonstrate that patients with PD maintain or even improve their postural control in all positions. We think that the main factor influencing these results is that patients use more of their available cognitive processing to improve their postural control. The ABAR system allows us to make this assumption because the system requires the continuous attention of patients, promoting cognitive processing.
Keywords: Parkinson’s disease; spatial postural control; motor symptoms; virtual motor rehabilitation; virtual reality